Technological solution of oil and gas waste disposal (Academic journal Industrial Machine Building Civil Engineering, 2022)
Technological solutions for the construction of sludge barns at the Pereschepynskoye deposit are considered and analyzed. The authors proposed to arrange a monolithic vertical anti-filtration curtain of the type "wall in the soil" of soil-cement elements. When filling the sludge storage, it is proposed to fill with waste using the following technology: pour a layer of waste about 1 m thick on the bottom of the sludge storage, then pour a layer of soil on top of the construction site (humidity 4-5%) up to 1 m. drying it is offered to add ash of removal of the Mykolaiv thermal power plant. The amount of additive is from 1.5 to 3% depending on the type of soil. The thickness of the layers is selected and calculated to obtain the optimum moisture content of the sludge and soil mixture
Keywords: soil cement; removal ash; strength; soil; cement